A Comprehensive Multi-Sector Tool for Analysis of Systemic Risk and Interconnectedness (SyRIN) - Cortes, Fabio (IMF Working Papers; Working Paper ;, 2018)
This paper presents the Systemic Risk and Interconnectedness (SyRIN) tool. SyRIN allows a comprehensive assessment of systemic risk via quantification of the impact of risk amplification mechanisms, due to interconnectedness structures across banks and other financial intermediaries-insurance, pension fund, hedge fund and investment fund sectors, which cannot be captured when analyzing sectors independently. The tool produces various metrics to evaluate systemic risk from complementary perspectives, including tail risk, cross-entity interconnectedness and the contribution to systemic risk by different entities and sectors. SyRIN is easily implementable with publicly available data and can be adapted to cater to different degrees of institutional granularity and data availability. The framework is designed to be a tool to identify vulnerabilities from a top-down perspective that can lead to deeper analysis in specific sectors for policy formulation.